2017
DOI: 10.1002/mabi.201700016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Tyrosine‐Triazolinedione (TAD) Reactions for the Selective Conjugation and Cross‐Linking of N‐Carboxyanhydride (NCA) Derived Synthetic Copolypeptides

Abstract: Highly efficient functionalization and cross-linking of polypeptides is achieved via tyrosine-triazolinedione (TAD) conjugation chemistry. The feasibility of the reaction is demonstrated by the reaction of 4-phenyl-1,2,4-triazoline-3,5-dione (PTAD) with tyrosine containing block copolymer poly(ethylene glycol)-Tyr as well as a statistical copolymer of tyrosine and lysine (poly(Lys -st-Tyr )) prepared form N-carboxyanhydride polymerization. Selective reaction of PTAD with the tyrosine units is obtained and veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…Gelatin can be easily dissolved in aqueous solutions above 37 °C; however, TADs are reported to undergo degradation in water [50], despite a certain stability of some TADs in aqueous medium reported in bioconjugation reactions by PTAD [56] or in cross-linking reaction of a synthetic Lys-Tyr polypeptide in TRIS buffer solution by difunctional TAD 2 [53]. In our hands both 1 and 2 almost immediately decomposed in any type of aqueous environment, as clearly indicated by the disappearing of their characteristic fuchsia color in a few seconds (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin can be easily dissolved in aqueous solutions above 37 °C; however, TADs are reported to undergo degradation in water [50], despite a certain stability of some TADs in aqueous medium reported in bioconjugation reactions by PTAD [56] or in cross-linking reaction of a synthetic Lys-Tyr polypeptide in TRIS buffer solution by difunctional TAD 2 [53]. In our hands both 1 and 2 almost immediately decomposed in any type of aqueous environment, as clearly indicated by the disappearing of their characteristic fuchsia color in a few seconds (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Triazolinedione ene-type chemistry recently emerged as a click-reaction for the bioconjugation to tyrosine residues, mediated by cyclic monofunctional diazodicarboxamides, such as 4-phenyl-1,2,4-triazoline-3,5-dione (PTAD) [48,49,50,51]. Hetherobifunctional triazolinediones (TADs), have been used for the synthesis of DNA−protein conjugates [52], while homobifunctional TADs have been applied to the cross-linking of synthetic polypetides [53].…”
Section: Introductionmentioning
confidence: 99%
“…8,13 Herein we report the synthesis of protein nanocapsules that were crosslinked with a 4-phenyl-triazolinedione (TAD) derivative, which specifically reacts with amino acids with delocalized π-electron systems. [14][15][16][17] The ability of TAD to act as a strong dienophile in a Diels-Alder reaction has already been shown almost 60 years ago. 18 Recent studies performed by Du Prez and coworkers again showed its versatility in current applications in polymer science.…”
Section: Introductionmentioning
confidence: 99%
“…As the double bond is preserved in the Alder–ene reaction, further functionalisation can be undertaken utilising the shifted double bond. TADs have been used to modify unsaturated polymers [32], prepare films [33], produce hydrogels [34,35] and produce crosslinked nanostructures [36]. In one example, a bis-functional TAD was applied to unsaturated fatty acids to produce crosslinked films from vegetable oils [37,38].…”
Section: Introductionmentioning
confidence: 99%